Fusion of Active Appearance Model and Histogram of Oriented Gradient for Age Estimation - Chang, Quan Yan; Ong, Thian Song; Chong, Siew Chin (International Journal of Engineering and Technology, 2018)
In recent years, automated age estimation through face images has attracted the interest among the research due to its variety applications in law enforcement, human computer interaction etc. This paper presents the fusion of Active Appearances Model (AAM) with Histogram of Oriented Gradients (HOG) to form the face descriptors for automatic age estimation. AAM and HOG are known to be reliable feature extraction techniques for shape and texture images. The weaknesses of both are minimized and the strengths of both are utilized in the proposed method for better age estimation model. The proposed method is evaluated using two benchmarked age estimation datasets and promising results is generated.